Flower-shaped ZnO nanomaterials for low-temperature operations in NOX gas sensors. Issue 5 (1st April 2020) - Nundy, Srijita; Eom, Tae-yil; Kang, Jun-gu; Suh, Jaehyun; Cho, Minwoo; Park, Joon-Shik; Lee, Hoo-Jeong
Abstract: In this study, we synthesized nanostructured zinc oxide (ZnO) by using various concentrations (0–0.05 M) of cetyltrimethylammonium bromide (CTAB) as a surfactant to optimize its morphology for gas sensor applications. The optimization process was used to elucidate the morphology effects (rod-shaped and flower-shaped morphologies). The morphologies were investigated through scanning electron microscopy, in which the assembly of nanorods leading to a spherical microstructure with a CTAB concentration of 0.005 M was observed. Brunauer–Emmett–Teller isotherm measurements revealed a surface area of 7.928 g/m 2 for the flower-like morphology, which was relatively higher than those of other CTAB-assisted morphologies. Such morphological features were expected to contribute toward high-performance gas-sensing. The effect of morphology variation on the resistance of ZnO microstructures was used for gas measurements. Among the varied morphologies, a sample with a spherical flower-shaped morphology exhibited a very high response at low temperatures ( 29 at 25 °C) toward NOX gas (0.75 ppm) and a high selectivity toward NOx among ammonia (NH3 ), toluene (C6 H5 CH3 ), carbon monoxide (CO), acetone (CH3 COCH3 ), and ethanol (C2 H5 OH). Raman and photoluminescence spectroscopy analyses unraveled the presence of a high density of oxygen vacancies in the sample, thereby suggesting a close link between the defective nature of the sample and the high response of the flower-like ZnO at low temperatures. Graphical abstract: Development of selective and sensitive ZnO-based NOX gas sensors operating at low temperatures.Synthesis of spherical flower-shaped ZnO with CTAB as the sensing material.Excellent sensitivity of 29 toward NOX at 25 °C.Low concentration (0.19–0.74 ppm) detection of NOX at 25 °C. Highly selectivity toward NOX among NH3, C6 H5 CH3, CO, CH3 COCH3, and C2 H5 OH at 25 °C. Image 1